A clean and green approach for odd chain fatty acids production in Rhodococcus sp. YHY01 by medium engineering. (August 2019) - Bhatia, Shashi Kant; Gurav, Ranjit; Choi, Tae-Rim; Han, Yeong Hoon; Park, Ye-Lim; Jung, Hye-Rim; Yang, Soo-Yeon; Song, Hun-Suk; Yang, Yung-Hun
Graphical abstract: Highlights: Rhodococcus sp. YHY01 can utilize propionate as a carbon source. Propionate act as a precursor for odd chain fatty acids. Glycerol feeding along with propionate enhance odd chain fatty acids content. Medium engineering resulted in fatty acids composed of 85% odd chain fatty acids. Abstract: Odd chain fatty acids serve as anti-allergic, anti-inflammatory, and antifungal agents, and are useful for the production of biodiesel. Rhodococcus sp. YHY01 utilizes a wide range of carbon sources and accumulate lipids i.e. fructose (37% w/w dcw) glucose (56% w/w dcw), glycerol (50% w/w dcw), acetate (42% w/w dcw), butyrate (65% w/w dcw), lactate (56% w/w dcw), and propionate (62% w/w dcw). In this study, propionate was proved as the best carbon source and produced 69% odd chain fatty acids of total fatty acids, followed by glycerol (13% odd chain fatty acids of total fatty acids). A synthetic medium optimized with response surface design containing glycerol, propionate, and ammonium chloride (0.32%:0.76%:0.040% w/v) facilitated the production of total fatty acids 69% w/w of dcw, and odd chain fatty acids comprised 85% w/w of total fatty acids. Major odd chain fatty acids were in the order C17:0 > C15:0 > Cis-10-C17:1 > 10Me-C17:0 > C19:0 > Cis-10-C19:1.